3088 – DISSECTING THE ONTOGENIC REMODELING OF THE PROTEOMIC LANDSCAPE AND FUNCTIONALITY OF HEMATOPOIETIC PROGENITOR CELLS IN NORMAL DEVELOPMENT AND LEUKEMIA - Jassinskaja, Maria; Pimková, Kristýna; Daher, Ugarit; Johansson, Emil; Eldeeb, Mohamed; Sitnicka, Ewa; Bryder, David; Hansson, Jenny (Experimental hematology, 2020)
The process of hematopoiesis is subject to extensive ontogenic remodeling that is accompanied by alterations in cellular fate both during normal development and disease. Although the functional differences between fetal and adult hematopoiesis are well established, the responsible molecular mechanisms have long remained largely unexplored on the proteomic level. In our latest work, we characterized and compared the proteomic makeup of fetal and adult HSPCs (Jassinskaja et al., 2017, Cell Reports). Here, we have utilized state-of-the-art mass spectrometry to gain deep coverage of the proteome of 100,000 fetal and adult lymphoid-primed multipotent progenitors (LMPPs), common lymphoid progenitors (CLPs) and granulocyte-monocyte progenitors (GMPs). Our analysis resulted in the identification and quantification of over 4000 proteins, with 200-300 proteins per cell type displaying differential expression between the fetus and the adult. We uncovered ontogenic changes in expression of several transcription factors with critical roles in hematopoiesis. Together with other proteins involved in lineage commitment and differentiation, we show that protein expression in fetal and adult hematopoietic progenitor cells is predictive of differential lineage potential. Our subsequent functional analyses further emphasize that the proteomic differences affect cell fate both in the context of normal differentiation and leukemic hematopoiesis driven by the MLL-ENL fusion oncogene. Collectively, our work represents a significant advancement in the understanding of the molecular programs that govern ontogenic differences in hematopoiesis and provides a solid foundation for future investigation of which factors are responsible for the difference in susceptibility and outcome of different leukemias in infants and in adults.